Management of Rheumatoid Arthritis through Ayurveda – A Case Study - H, Rahul; Gouri, P S; Narayanan, P Sreeda (International Research Journal of Ayurveda & Yoga, 2024)
Rheumatoid arthritis is a chronic inflammatory disease of joints with unknown etiology. It manifests as symmetrical, peripheral polyarthritis. It is more common in females than in males with a 3:1 ratio. According to WHO in 2019 the prevalence of people living with rheumatoid arthritis was around 18 million. The development of the disease may be triggered by genetic predisposition along with environmental factors and is prolonged with intermittent exacerbations and remissions. While there is no cure, physiotherapy and medications can help to slow the disease progression. On the basis of signs and symptoms, it can be correlated with Amavata described in Ayurveda and the followed treatments are from classic Amavata Chikitsa. The article deals with management of a case of Amavata through Ayurveda. This study is about a previously diagnosed male patient with rheumatoid arthritis who had strictly followed diets and regimens, when neglected the routine lead to recurrence of disease which became difficult to manage by him. In an attempt to attain Amapachana Agni was initially corrected with the help of internal medicine. External Panchakarma therapies were planned in order to eliminate the lodged Doshas from Shaka. As a result, the patient showed reduction in symptoms. Additionally, patient was advised to follow Pathya. The outcome was remarkable and worth documenting. Assessment was done with specific criteria before and after treatment Thus, description of this case aims to provide assistance to the patients to have a healthy lifestyle, incorporating Ayurveda, thereby reducing the severity and frequency of symptoms of the disease.